Heartbeat: The gut microbiota and heart failure - Otto, C; Rahimi, K (BMJ Publishing Group, 2016)
Patients with acute heart failure are at high risk of adverse clinical outcomes. Although elevated levels of trimethylamine N-oxide (TMAO), a gut-derived metabolite, have been shown to be independently associated with cardiovascular disease and poor outcomes in stable heart failure patients, their role in patients with acute heart failure is not well understood. In this issue of Heart, Suzuki and colleagues (see page 841) investigate this question further and show that the addition of TMAO to established multivariable risk models led to better stratification of acute heart failure patients’ risk of in-hospital mortality (figure 1). However, the association was attenuated when renal function was added to the models.